Perbandingan Akurasi Model Altman, Zmijewski, dan Grover untuk Memprediksi Financial Distress Industri Media Hiburan - Hana Nur Rofiah; Sri Luna Murdianingrum (Owner : Riset dan Jurnal Akuntansi, 2026)
Financial distress is a condition in which a company experiences financial pressure and, if not properly addressed, can lead to insolvency. The media and entertainment industry is particularly vulnerable to this situation. This study aims to determine which financial distress prediction model is more accurate for the entertainment media industry. The models used in this study are the Modified Altman Z-Score Model, the Zmijewski Model, and the Grover Model. Fourteen media and entertainment companies were sampled for the study between 2020 and 2024. The predicted data from the three models were compared with actual conditions, with indicators of negative net profit and negative operating cash flow simultaneously. The results showed that the Zmijewski model had the highest accuracy rate of 75.7%, followed by the Grover model with an accuracy rate of 70%, and the Altman model with an accuracy rate of 62.9%.